Black carbon effects and seasonal isotope records in the Godwin-Austen snowpack and K2 high-altitude camps - Nicolás González-Santacruz; Francisco Fernandoy; Kumiko Goto-Azuma; Motohiro Hirabayashi; Raul R. Cordero; Sarah Feron; Sérgio Henrique Faria (Journal of Glaciology)
This study investigates black carbon (BC) concentrations in the seasonal snowpack on the Godwin-Austen Glacier and in surface snow at K2 Camps 1 and 2 (Karakoram Range), assessing their impact on snowmelt during the 2019 ablation season. Potential BC and moisture sources were identified through back-trajectory analysis and atmospheric reanalyses. Variations in water stable isotopes (δ1⁸O and δ2H) in the snowpack were analysed to confirm its representativeness as a climatic record for the 2018–19 accumulation season. The average BC concentration in the snow pits (12 ng g−1) generated 66 mm w.e. (or 53 mm w.e. excluding the basal zone) of meltwater. Surface snow at K2 Camp 1 showed BC concentrations of 7 ng g−1, consistent with those on the snowpack surface, suggesting it may reflect local BC levels in late February 2019. In contrast, higher concentrations at K2 Camp 2 (26 ng g−1) were potentially linked to expedition activities.